CUBIC SPLINES IN THE GRASSMANN MANIFOLD GENERATED BY THE DE CASTELJAU ALGORITHM - Pina, Fátima (2020)
We present a detailed analysis of the De Casteljau algorithm to gen erate cubic polynomials satisfying certain boundary conditions in the Grassmann manifold, and extend this approach to produce cubic splines that also solve inter polation problems on that manifold.